Noninvasive hemoglobin quantification across different cohorts using a wearable diffuse reflectance spectroscopy system - Chen, Ying-Yu; Lai, Guan-Hua; Chen, Chia-Te; Cheng, Hsiu-Chi; Tseng, Sheng-Hao (Biomedical optics express, 2024)
Quantifying hemoglobin is vital yet invasive through blood draws. We developed a wearable diffuse reflectance spectroscopy device comprising control and sensor boards with photodiodes and light-emitting diodes to noninvasively determine hemoglobin. Neural networks enabled recovery of optical parameters for chromophore fitting to calculate hemoglobin. Testing healthy and elderly subjects revealed strong correlation (r=0.9) between our system and invasive methods after data conversion. Bland-Altman analysis demonstrated tight 95% limits of agreement from −1.98 to 1.98 g/dL between the DRS and invasive hemoglobin concentrations. By spectroscopically isolating hemoglobin absorption, interference from melanin was overcome. Our device has the potential for future integration into wearable technology, enabling hemoglobin level tracking.